(untitled) (Leiden, Neitherlands, 1997)
The book deals with the auxiliary plants in agriculture and forestry of South-East Asia, including fuelwoods and water-clearing plants. Auxiliary plants have service functions in cropping systems and help increase or sustain the yield of the main crops. Auxiliary plants include shade and nurse trees, cover crops, green manures, mulch, fallow crops, live fences, wind-breaks and shelter-belts, live supports and stakes, erosion-controlling plants and land reclamation species. Fuelwoods are treated here, as many of the trees and shrubs used for fuel, such as Leucaena leucocephala, Casuarina spp. and Acacia spp. have auxiliary roles too. Fuel also plays an auxiliary role in many production processes, contributing to but not forming part of the end product. Water-clearing plants are not used in South-East Asia as commonly as in Africa or Europe, where ponds and canals bordered with Phragmites spp. contribute significantly to the clearing of effluents. Most of the 78 important crops treated in this book are grown in South-East asia, but several crops widely grown elsewhere and potentially useful in parts of South-East Asia have been included as well. A further 107 genera and species of minor importance are treated briefly, while over 150 species which play an auxiliary role or provide fuelwood but have another primary use are listed
Keywords: Tropical plants,Cây nhiệt đới